2012
DOI: 10.4196/kjpp.2012.16.5.313
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Eupatilin against Hydrogen Peroxide-Induced Injury Involving 5-Lipoxygenase in Feline Esophageal Epithelial Cells

Abstract: In this study, we focused to identify whether eupatilin (5,7-dihydroxy-3',4',6-trimethoxyflavone), an extract from Artemisia argyi folium, prevents H2O2-induced injury of cultured feline esophageal epithelial cells. Cell viability was measured by the conventional MTT reduction assay. Western blot analysis was performed to investigate the expression of 5-lipoxygenase by H2O2 treatment in the absence and presence of inhibitors. When cells were exposed to 600 µM H2O2 for 24 hours, cell viability was decreased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…eupatilin, a dietary flavone compound, has anti-ulcer, anti-inflammatory and cell cycle regulator inhibitory effects (6,8,36). Accumulating evidence shows that eupatilin has antitumor function against the different types of cancer, including gastric and endometrial cancer (36). In the present study, we found that eupatilin could inhibit JB6 cell proliferation and growth in a dose-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…eupatilin, a dietary flavone compound, has anti-ulcer, anti-inflammatory and cell cycle regulator inhibitory effects (6,8,36). Accumulating evidence shows that eupatilin has antitumor function against the different types of cancer, including gastric and endometrial cancer (36). In the present study, we found that eupatilin could inhibit JB6 cell proliferation and growth in a dose-dependent manner (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…Flavonoids are well known as promising chemopreventive agents against human cancers. eupatilin, a dietary flavone compound, has anti-ulcer, anti-inflammatory and cell cycle regulator inhibitory effects (6,8,36). Accumulating evidence shows that eupatilin has antitumor function against the different types of cancer, including gastric and endometrial cancer (36).…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxicities were measured with the MTT-based colorimetric assay as described in the Table 1 legend [28-31]. …”
Section: Methodsmentioning
confidence: 99%
“…Eupatilin is a flavonoid isolated from Artemisia princeps Pampanini (Asteraceae) [10]. It possesses strong antioxidant and antiinflammatory properties [11,12]. Moreover, it has been reported that eupatilin exerts gastroprotective effects by attenuating gastric mucosal injuries [13].…”
Section: Introductionmentioning
confidence: 99%